A propósito del artículo “Intervención educativa sobre sífilis en el Establecimiento Penitenciario Provincial de Ciego de Ávila” - González Tapia, Margarita; Vivas Bombino, Luis (Mediciego, 2019)
The article published in the MediCiego 2019 journal, Vol. 25 No. 1, “Educational intervention on syphilis in the Provincial Penitentiary Establishment of Ciego de Ávila”,(1) is interesting, both for its content and for what it represents for Cuban public health the topic discussed.